Maximal subsemigroups and finiteness conditions on transformation semigroups with fixed sets - Yanisa Chaiya (2018)
© Tübitak. Let Y be a fixed subset of a nonempty set X and let Fix(X, Y ) be the set of all self maps on X which fix all elements in Y . Then under the composition of maps, Fix(X, Y ) is a regular monoid. In this paper, we prove that there are only three types of maximal subsemigroups of Fix (X, Y ) and these maximal subsemigroups coincide with the maximal regular subsemigroups when X \ Y is a finite set with |X \ Y | ≥ 2. We also give necessary and sufficient conditions for Fix(X, Y ) to be factorizable, unit-regular, and directly finite.